2000
DOI: 10.1007/bf03027304
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and theoretical analysis of the adsorption of supercritical methane on superactivated carbon

Abstract: Adsorption/desorption isotherms of supercritical methane on superactivated carbon have been measured in the range of 0 10 MPa and 233 333 K (20 K interval). The reversibility of the physical adsorption process is acknowledged. The heat of adsorption of 16.5 kJ/mol is determined from the isotherms, and a new modeling strategy for isotherms with maximum is presented. The model yields fits to the experimental isotherms with precision of 2%, maintaining the constancy of the characteristic energy of adsorption. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 11 publications
(14 reference statements)
2
25
0
Order By: Relevance
“…It was observed that the adsorbed density is always higher than the gaseous methane density at the same temperature, but lower than the liquid methane density (26.33 mmol/cm 3 ). This finding agrees with the most widely accepted fact that the density of adsorbed phase should always be lower than the liquid phase density, but higher than the gaseous phase density. , …”
Section: Resultssupporting
confidence: 89%
“…It was observed that the adsorbed density is always higher than the gaseous methane density at the same temperature, but lower than the liquid methane density (26.33 mmol/cm 3 ). This finding agrees with the most widely accepted fact that the density of adsorbed phase should always be lower than the liquid phase density, but higher than the gaseous phase density. , …”
Section: Resultssupporting
confidence: 89%
“…First, the adsorbent possesses a high specific surface area; therefore, the maximum could appear at relatively lower pressures for a given temperature. Second, a systematic monitoring of the adsorption behavior is made over the range of 103 to 298 K with increments of 20 K. A volumetric setup employed in the studies on the adsorption of hydrogen and methane (10,11) was used to measure the excess adsorption of nitrogen. The temperature of the cryostat was kept constant to within ±(0.1-0.5) K at any specified temperature for the experimental range.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is difficult to set up a thermodynamically standard state for the adsorbed phase of supercritical gas. The standard state usually refers to the liquid-like state of gas for subcritical gas adsorption processes, however, this assumption is not valid for supercritical fluids (Zhou et al, 2000a(Zhou et al, & 2000bZhou et al, 2009). Moreover, using the liquid methane density or quasi-liquid density to extrapolate the absolute adsorption uptake from directly measured data is questionable even though previous works assert that the assumption allows researchers to investigate adsorption thermodynamics by considering both real gas behavior and the effect of adsorbed phase (Mertens et al, 2009;Stadie et al, 2013;Stadie et al, 2015;Tang et al, 2017aTang et al, , 2017bTang et al, & 2017cMurialdo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The first assumption assumes the pore structure does not change during adsorption, and that adsorption induced deformation is beyond the scope of this work (Gor et al, 2017). The second assumption is well-known and has been validated by many researchers (Zhou et al, 2000a(Zhou et al, & 2000bMurata et al, 2001;Mertens et al, 2009;Do et al, 2003;Thommes et al, 2015). For the third assumption, the intrinsic adsorption capacity refers to the limiting adsorption uptake under limiting pressure, which is determined by pore structure, surface chemistry of the pore and molecular size of the adsorbate (Zhou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%